Economic footprint assessment of storm surge disasters in China based on disastrously-extended input-output analysis - Han, Rui; Yin, Kedong; Dai, Xin; Li, Huishang; Zhou, Shiwei (Frontiers in Marine Science, 2025)
IntroductionEscalating climate change has intensified storm surge disasters in China, whose economic repercussions are not confined to coastal areas but cascade nationwide through industrial supply chains. However, existing research overlooks these nationwide implications.MethodsTo address this gap, this paper proposes an innovative assessment framework for evaluating the economic footprint of storm surge disasters, quantifies the indirect economic losses inflicted by storm surge disasters in China from 2011 to 2020 and further trace the diffusion of these losses across various industries and regions by developing a disastrously-extended input-output model.ResultsThe findings reveal that indirect economic losses constituted over 60% of the total economic losses from storm surge disasters during the aforementioned period. Interestingly, regions remote from the direct impact of the storm surge disasters were not immune to their effects. Among these, Henan Province emerged as the inland area most severely impacted by storm surge disasters, while the northwest and southwest regions typically experienced minimal indirect economic losses. Furthermore, the majority of the indirect economic losses originated from the Resource Processing Industry and Service Department of the directly affected regions, and the secondary industry of the potentially affected regions.DiscussionThese findings demonstrate the inadequacy of localized disaster policies and underscore the urgent need for a nationwide resilience strategy focused on critical supply chain vulnerabilities.